Rekonstruksi Perlindungan Hukum Konsumen terhadap Klausula Baku dan Praktik Usaha Curang dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 - Gusti Ayu Marantika; Cisilia Tyas Ikasari; Hambrian Wijaya; Anatasya Auliya Azka Hamidah; Yuyut Prayuti (Universitas Muhammadiyah Manado, 2026)
The imbalance in bargaining position between business actors and consumers frequently places consumers in a vulnerable position to economic exploitation through the inclusion of standard clauses and unfair trade practices. This study aims to analyze the fulfillment of rights and obligations of the parties, identify the comprehensive boundaries of prohibited acts for business actors, and examine the legal binding force of standard clauses in commercial transactions under Law Number 8 of 1999 concerning Consumer Protection (UUPK). The method employed in this research is a normative juridical legal approach with statutory and conceptual analysis, utilizing qualitative analysis of secondary data obtained from library research combined with a deductive reasoning method. The findings underscore two pivotal aspects. First, the weak standing of consumers in the market is driven not only by economic imbalances but also by low legal awareness and minimal information transparency regarding quality standardization. Second, the inclusion of standard clauses that unilaterally transfer liability (exculpatory clauses) is strictly prohibited by Article 18 of UUPK and declared null and void, which aligns with the progressive judicial stance in the landmark Supreme Court Civil Judicial Review Decision Number 124/PK/PDT/2007. The theoretical implication of this study urges a reconstruction of the freedom of contract doctrine bounded by distributive justice, while its practical implication recommends the government, YLKI, and BPKN to tighten preventive oversight through auditing draft standard agreements in public spaces and formulating adaptive regulations toward digital contract disruptions.